Humorn i stadens mångstämmiga rum: En läsning av romanen Markurells i Wadköping av Hjalmar Bergman - Ciaravolo, Massimo (Tidskrift för litteraturvetenskap, 2023)
“Humour in the Polyphonic Town Space. A Reading of Hjalmar Bergman’s Novel The Markurells of Wadköping” The novelist as an accomplished artist is revealed, in Mikhail Bakhtin’s view, when the stamp of his/her voice and style is kept while interacting and intermingling with other voices and styles expressed in the novel, often taken from social, collective spaces such as the town. In addition, Bakhtin observes that a history of laughter can be read in the development of the novel as a genre. With its popular roots in carnival traditions, the novel takes place in streets and market squares, and creates an alternative social place which can overturn given social, political and economic hierarchies. Furthermore, the literary scholar Leo Spitzer shows how a novel’s narrator voice can borrow and mould the common voice of a whole community of speakers, as a sort of choir, for instance, in a village or a small town, through the use of free indirect speech (erlebte Rede). By following these stylistic clues, the article examines how comic, grotesque and fantastic effects are triggered in Hjalmar Bergman’s novel The Markurells of Wadköping, especially in case of ‘polyphonic’ scenes in which the small town participates as a unit, and as a receptive and collective conscience. When humour is in great style, it also contains a tragic dimension, as suggested by the philosopher Simon Critchley. Bergman’s humour is marked by pessimism, and the writer is ambivalent towards the apparently solid, bourgeois world prior to World War I which he comes from and depicts in his novel. The author feels close to this world and describes it with empathy, but at the same time he displays a critical distance as well as a need to part from it. The ‘polyphonic’ plurality of voices in this novel refers also to such an inner conflict. In the article, Hjalmar Bergman is considered as an interpreter of existential disharmony and shortcomings, but also as a writer who found in laughter a form of love for life despite everything.